The Hexavalent CD40 Agonist HERA-CD40L Induces T-Cell–mediated Antitumor Immune Response Through Activation of Antigen-presenting Cells. Issue 9 (November 2018) - Merz, Christian; Sykora, Jaromir; Marschall, Viola; Richards, David M.; Heinonen, Karl; Redondo Müller, Mauricio; Thiemann, Meinolf; Schnyder, Tim; Fricke, Harald; Hill, Oliver; Gieffers, Christian
Abstract : CD40 ligand (TNFSF5/CD154/CD40L), a member of the tumor necrosis factor (TNF) superfamily is a key regulator of the immune system. The cognate receptor CD40 (TNFRSF5) is expressed broadly on antigen-presenting cells and many tumor types, and has emerged as an attractive target for immunologic cancer treatment. Most of the CD40 targeting drugs in clinical development are antibodies which display some disadvantages: their activity typically depends on Fcγ receptor–mediated crosslinking, and depletion of CD40-expressing immune cells by antibody-dependent cellular cytotoxicity compromises an efficient antitumor response. To overcome the inadequacies of antibodies, we have developed the hexavalent receptor agonist (HERA) Technology. HERA compounds are fusion proteins composed of 3 receptor binding domains in a single chain arrangement, linked to an Fc-silenced human IgG1 thereby generating a hexavalent molecule. HERA-CD40L provides efficient receptor agonism on CD40-expressing cells and, importantly, does not require FcγR-mediated crosslinking. Strong activation of NFκB signaling was observed upon treatment of B cells with HERA-CD40L. Monocyte treatment with HERA-CD40L promoted differentiation towards the M1 spectrum and repolarization of M2 spectrum macrophages towards the M1 spectrum phenotype. Treatment of in vitro co-cultures of T and B cells with HERA-CD40L–triggered robust antitumor activation of T cells, which depended upon direct interaction with B cells. In contrast, bivalent anti-CD40 antibodies and trivalent soluble CD40L displayed weak activity which critically depended on crosslinking. In vivo, a murine surrogate of HERA-CD40L–stimulated clonal expansion of OT-I–specific murine CD8 + T cells and showed single agent antitumor activity in the CD40 − syngeneic MC38-CEA mouse model of colorectal cancer, suggesting an involvement of the immune system in controlling tumor growth. We conclude that HERA-CD40L is able to establish robust antitumor immune responses both in vitro and in vivo. Abstract : Supplemental Digital Content is available in the text.